Post-operative Functional Outcome in Fracture Distal Shaft of Femur Treated with Retrograde Nailing - Muhammad Sheraz , Riaz Ahmed , Muhammad Omer Kaleem, Muhammad Sheraz , Riaz Ahmed , Muhammad Omer Kaleem (Journal of Rawalpindi Medical College, 2019)
Background: To determine the functional outcome of retrograde femoral nailing in terms of Tegner Lysholm score for distal femoral farctures. Methods: This prospective cross-sectional study was done at the Department of Orthopaedics, Benazir Bhutto Hospital, Rawalpindi from 20th January 2018 to 19th January 2019. The study comprised of 35 patients who presented with simple, extra-articular distal femur fracture. All patients were treated with retrograde femoral nailing using anterior (Para patellar) approach. Functional outcome was assessed at 6-months using Tegner Lysholm score. Data was analyzed using SPSS version 22. Results: Out of the 35 patients, majority were females (60%). Mean age of patients was 51.4±11.4 years. Most common age group in males was 41-50 years while in females it was 61 years and above. Average BMI of patients was 22.7±2.8 kg/m2. At 6-months post-operatively, Tegner Lysholm score was between 86-100, 71-85 and 56-70 in 65.7%, 25.7% and 8.6% cases, respectively. Tegner Lysholm score between genders was insignificant (p=0.4). Conclusion: Retrograde femoral nailing has excellent functional outcome in patients with extra-articular distal femoral fractures.